Antibacterial activity of ethanol extract of Beluntas leaves on Streptococcus mutans, Porphyromonas gingivalis, and Enterococcus faecalis - Sylvana, Dini; Amir, Masyhudi; Purnamasari, Cicih Bhakti; Iskandar, Abdillah; Asfirizal, Verry (Padjadjaran Journal of Dentistry, 2021)
Introduction: Individuals with poor oral health have a greater risk factor for systemic diseases. Caries, periodontal disease, and root canal infections are a common dental and oral diseases caused by dominance of Streptococcus mutans, Porphyromonas gingivalis, and Enterococcus faecalis bacteria (S. mutans, P. gingivalis, and E. faecalis). An alternative way to prevent dental and oral diseases is to use herbal medicine as one of the active ingredients for mouthwash or toothpaste. One of the herbs that can be used is Beluntas leaves (Pluchea indica (L.) Less leaves). The objective of study was to analyze the antibacterial activity of ethanol extract of Pluchea indica (L.) Less leaves on the growth of Streptococcus mutans, Porphyromonas gingivalis, and Enterococcus faecalis. Methods: This research was experimental laboratory with post test only control design, using disk diffusion method. There were five concentrations (2.5, 3.5, 4.5, 5.5 and 6.5%, positive controls, and negative controls. Data analysis was performed using One Way Anova and post Hoc test. Results: The ethanol extract of Pluchea indica (L.) Less leaves has moderate-strong antibacterial activity against Streptococcus mutans, Porphyromonas gingivalis, and Enterococcus faecalis. The largest diameter of inhibitory zone in Enterococcus faecalis at a concentration of 6.5% followed by Streptococcus mutans and Porphyromonas gingivalis at the same concentration and the smallest diameter of inhibition zone in Porphyromonas gingivalis, followed by Enterococcus faecalis and Streptococcus mutans at 2.5% concentration. Conclusion: The ethanol extract of Pluchea indica (L.) Less leaves with a concentration of 2.5, 3.5, 4.5, 5.5, and 6.5% has antibacterial activity in inhibiting the growth of Streptococcus mutans, Porphyromonas gingivalis, and Enterococcus faecalis.